Social Enterprise: The Alternatives Financial Support For Educational Institusion - Siahaan, Daniar; Iswati, Sri; Zarkasyi, Amal Fathullah (International Journal of Economics and Financial Issues, 2019)
Enterprise social in the context of education is one of the innovations in maintaining the financial resources of an educational institution. In this study, social enterprise sustainability was used to realize a social enterprise-based boarding school management system, as well as supporting education improvement in Gontor Islamic Boarding School. This research method is action research to find out how the sustainability model of social enterprise implementation is carried out by Gontor. The results of the study show that enterprise social sustainability has shown success in providing benefits to the institution and society. Keywords: Social Enterprise, Pesantren, Gontor, Financial Support JEL Classifications: O35, G2, I23 DOI: https://doi.org/10.32479/ijefi.7626